Huston Thompson papers - Thompson, Huston; United States. Federal Trade Commission
Correspondence, letterbooks, diaries, speeches, articles, photographs, printed matter, and other papers relating to Thompson's service as legal counsel in the investigation of the Tennessee Valley Authority in the 1930s and his service (1934-1952) as mediator in national industrial strike emergencies. Subjects include the New Deal and Fair Deal eras, securities legislation, the U.S. Federal Trade Commission, and Woodrow Wilson. Correspondents include Helen Woodrow Bones, John W. Davis, Robert Lansing, Eleanor Wilson McAdoo, W.G. McAdoo, Franklin D. Roosevelt, Harry S. Truman, Willis Van Devanter, Edith Bolling Galt Wilson, and Woodrow Wilson.
Lawyer and government official.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bones, Helen Woodrow -- Correspondence; Davis, John W. -- 1873-1955 -- Correspondence; Lansing, Robert, -- 1864-1928 -- Correspondence; McAdoo, Eleanor Wilson, -- 1889-1967 -- Correspondence; McAdoo, W. G. -- 1863-1941 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Truman, Harry S., -- 1884-1972 -- Correspondence; Van Devanter, Willis, -- 1859-1941 -- Correspondence; Wilson, Edith Bolling Galt, -- 1872-1961 -- Correspondence; Wilson, Woodrow, -- 1856-1924.; Wilson, Woodrow, -- 1856-1924 -- Correspondence; Tennessee Valley Authority; Industries -- United States; Labor disputes -- United States; New Deal, 1933-1939.; Securities industry -- Law and legislation; Strikes and lockouts -- United States; United States -- History -- 1933-1945.; United States -- History -- 1945-1953.; United States -- Politics and government -- 1933-1945.; United States -- Politics and government -- 1945-1953.; United States -- Social conditions -- 1933-1945.; United States -- Social conditions -- 1945-; Lawyers; Public officials